2018
DOI: 10.1155/2018/8054284
|View full text |Cite
|
Sign up to set email alerts
|

Gastric MALT Lymphoma with Increased Plasma Cell Differentiation Showing Unique Endoscopic Features

Abstract: A 62-year-old woman was diagnosed with extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT lymphoma) with increased plasma cell differentiation of the stomach. Esophagogastroduodenoscopy showed slightly elevated, whitish lesions in the gastric body. Magnifying endoscopic observation revealed that the gastric surface epithelium was swollen, but the structure was not destroyed or diminished. Elongated, tortuous vasculature was observed on the surface of the whitish lesions. The patient u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…In our previous work, we have revealed that progression or relapse tended to be more frequent in patients with extra copies of MALT1 [30]. Conversely, MALT lymphoma with increased plasma cell differentiation shows favourable treatment response [31, 32]. Based on the outcome observed in Case 2 of the present report, careful follow-up may be necessary in patients with gastric MALT lymphoma resembling follicular gastritis to detect relapse.…”
Section: Discussionmentioning
confidence: 51%
“…In our previous work, we have revealed that progression or relapse tended to be more frequent in patients with extra copies of MALT1 [30]. Conversely, MALT lymphoma with increased plasma cell differentiation shows favourable treatment response [31, 32]. Based on the outcome observed in Case 2 of the present report, careful follow-up may be necessary in patients with gastric MALT lymphoma resembling follicular gastritis to detect relapse.…”
Section: Discussionmentioning
confidence: 51%
“…About 50–80% of cases are positive for CD79a. There is no expression of MyoD1, myogenin, myoglobin, desmin, or actin [18].…”
Section: Discussionmentioning
confidence: 99%
“…Myeloid sarcoma in the stomach is a localized tumor formed by extramedullary proliferation and infiltration of myeloid primordial cells or immature myeloid cells. These tumors are positive for MPO, lysozyme, CD68, and CD117, but negative for CD3, MyoD1, myogenin, and myoglobin [17][18][19][20][21][22][23].…”
mentioning
confidence: 99%